2019
DOI: 10.1177/1934578x19859977
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Their Activities From the Seeds of Ormosia hosiei

Abstract: A new cytisine-like alkaloid, hosimonoal (1), with a fused monoterpene group, and 6 known compounds (2-6) were isolated from the seeds of Ormosia hosiei Hemsl. et Wils. The structure of the new compound was confirmed by high resolution electrospray ionization mass spectroscopy (HRESIMS), 1D and 2D nuclear magnetic resonance (NMR) spectroscopy, and electronic circular dichroism, and the others by 1H and 13C NMR spectroscopy and comparison with the literature data. In addition, compounds 1, 2, 3, and 6 showed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Inherent reproductive limitations and external disturbances have sharply reduced its natural population, calling for urgent protection efforts [21]. Most studies of O. hosiei focus on genetic diversity [19,22], phytochemical composition [23,24], seedling cultivation [25,26], and ecology [27], furnishing a rich empirical and theoretical basis for species protection. However, phytogeography studies are lacking [28].…”
Section: Introductionmentioning
confidence: 99%
“…Inherent reproductive limitations and external disturbances have sharply reduced its natural population, calling for urgent protection efforts [21]. Most studies of O. hosiei focus on genetic diversity [19,22], phytochemical composition [23,24], seedling cultivation [25,26], and ecology [27], furnishing a rich empirical and theoretical basis for species protection. However, phytogeography studies are lacking [28].…”
Section: Introductionmentioning
confidence: 99%
“…We have been committed to researching the development and utilization of Ormosia plant resources. [3][4][5][6][7][8] Previously, we found that the extract of O. xylocarpa leaves showed promising antioxidant activity. To discover compounds with strong antioxidant activity, 8 compounds (1-8) were isolated from O. xylocarpa and their antioxidant activities tested.…”
Section: Introductionmentioning
confidence: 99%